Genetic Diversity Analysis of Dendrobium sp Orchid from Indonesia based on Random Amplified Polymorphic DNA (RAPD) - Ahmad Yunus; Sri Hartati; Fitria Riviqowati (Journal of Biodiversity and Biotechnology, 2026)
The orchid genus Dendrobium is a commodity from plants that are sold in pots, and Cut flowers are very popular in the world because they have flowers of various sizes, shapes, and colors. Orchid flowers of the Dendrobium genus flower throughout the year, so they are included in the promising cut flower industry. Information on genetic diversity and genetic relationships between orchids of the genus Dendrobium through molecular analysis techniques is needed in plant breeding programs and genetic resources. Orchids Dendrobium that have various phenotypes will increase the selling value of the commodity. The purpose of this study was to determine the genetic diversity of the orchid Dendrobium using RAPD markers. The scoring data were analyzed using NTSYS-pc (software Numeral Taxonomic System) version 2.02, which produced data in the form of cluster dendrograms. Genetic diversity of Dendrobium spp., analyzed with 5 primers RAPD, ranges from 43-76% and divides the dendrogram into 2 main clusters based on genetic similarity. The polymorphism of the 5 RAPD primers was very high, namely 91.6-100%.